Theoretical Investigation of Intersections of Metal-Insulator-Silicon-Insulator-Metal Waveguides - Min-Suk Kwon; Yonghan Kim (IEEE Photonics Journal)
We theoretically investigate simple, circle-shaped, and diamond-shaped intersections of metal-insulator-silicon-insulator-metal (MISIM) waveguides. Because of the strong light confinement of the hybrid plasmonic waveguides, the simple intersection does not work efficiently. The low efficiency of the simple intersection is improved in the other intersections, and the diamond-shaped intersection is superior to the circle-shaped one. When the footprint of the diamond-shaped intersection is just 1.96 μm2, its throughput is between –0.68 and –0.78 dB in the wavelength interval between 1.45 and 1.60 μ m, and its crosstalk is smaller than –18 dB in the interval. This compact, efficient intersection may pave the way to on-chip hybrid networks of photonic and plasmonic devices.